2020
DOI: 10.22541/au.160029789.93744641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and application of a novel topical anaesthetic wound formulation for treating cattle with Foot-and-Mouth disease: a field trial in Cameroon

Abstract: Recently, a wound dressing formulation, (Tri-Solfen®, Medical Ethics Pty Ltd, Australia; TS) registered for use in ruminant husbandry in Australia, was registered for Foot-and-Mouth Disease (FMD) therapy in large ruminants in Laos, following clinical observations of improved welfare and healing following treatment of FMD lesions. In November 2019, an FMD outbreak in Cameroon provided an opportunity for a field trial, comparing clinical responses and recoveries to treatments on a sample of cattle (n = 36) compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The comparison of the efficacy of Tri-Solfen and antimicrobial treatment (parenteral oxytetracycline) against FMD lesion healing under controlled conditions in a trial showed a 100% protective rate of both treatments towards clinical recovery, but with a more rapid healing observed for the new formulation compared to the parenteral oxytetracycline group [59].…”
Section: Foot-and-mouth Diseasementioning
confidence: 99%
“…The comparison of the efficacy of Tri-Solfen and antimicrobial treatment (parenteral oxytetracycline) against FMD lesion healing under controlled conditions in a trial showed a 100% protective rate of both treatments towards clinical recovery, but with a more rapid healing observed for the new formulation compared to the parenteral oxytetracycline group [59].…”
Section: Foot-and-mouth Diseasementioning
confidence: 99%
“…From the results of the first clinical trial of TS in Cameroon, farmer observations indicated that the TS treatment group had a more rapid return to eating with cessation of excessive salivation, and more rapid return of mobility (walking) with the absence of overt lameness compared to the commonly used antibiotic Moore-Oxy® (MO) (oxytetracycline HCL 5%, Hebei Kexing Pharmaceutical Co. Ltd., Shijiazhuang City, China) and the non-treated control group [18] . 100% of farmers expressed their desire that the product is made available for use in their region and cost-effective modelling indicated that TS therapy only costs 2.5 USD, imposes no additional financial burden on farmers, with the treatment likely to be provided at a similar or reduced cost to current treatment choices.…”
Section: Vaccinationmentioning
confidence: 99%
“…The risk-based control approach using the global progressive control pathway for FMD control (PCP-FMD) is the target for Cameroon as it is currently in the PCP-FMD stage one [7] . FMD transmission risk sources such as communal grazing, mobile livestock especially cattle, the role of carrier animals, role of fomites (a fomite is any material or object that can harbour an infectious disease and probably contaminate the environment and hosts), husbandry system, high livestock density, and the environment around herds, abattoirs and cattle markets have been examined and identified to be potential transmission areas to target for its mitigation [14][15][16][17][18] . The control of FMD in Cameroon is a major concern as no vaccination programs are ongoing and its management is mostly conducted by farmers themselves using veterinary pharmaceuticals mostly purchased from black markets and only a few of them buy from recognised pharmacies [17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation